1998
DOI: 10.3989/scimar.1998.62n4361
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: SUMMARY: Lengths of cnidae, sampled from fresh tissue (tentacles, acontia or column) from the sea anemones Metridium senile (Linnaeus), Cereus pedunculatus (Pennant), Sagartia elegans (Dalyell), Sagartia troglodytes (Price), Anthopleura thallia (Gosse) and Urticina eques (Gosse), were measured. The mean, mode, median, standard deviation, variance, coefficient of variation, minimum, maximum and range of each sample were calculated. Lengths of nematocysts (basitrichs and microbasic p-mastigophores) and spirocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We scanned through the slides and haphazardly chose 15 capsules of each type (when possible) to measure to generate a range: frequencies given are subjective impressions based on all the cnidae seen on the slides. For each type, a mean and standard deviation has been provided to give an idea of the distribution of sizes; these are not statistically significant (see Williams 1998Williams , 2000 for minimal requirements for statistical significance in cnida sizes) but provide some qualitative information about variability in capsule size for each type of nematocyst. Cnida terminology follows Mariscal (1974); however, we allude to Schmidt's (1969) terminology and correspondences between classifications because the latter is more detailed.…”
Section: Methodsmentioning
confidence: 99%
“…We scanned through the slides and haphazardly chose 15 capsules of each type (when possible) to measure to generate a range: frequencies given are subjective impressions based on all the cnidae seen on the slides. For each type, a mean and standard deviation has been provided to give an idea of the distribution of sizes; these are not statistically significant (see Williams 1998Williams , 2000 for minimal requirements for statistical significance in cnida sizes) but provide some qualitative information about variability in capsule size for each type of nematocyst. Cnida terminology follows Mariscal (1974); however, we allude to Schmidt's (1969) terminology and correspondences between classifications because the latter is more detailed.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding intra-structure variations, Williams (1996 , 1998 , 2000) analyzed the cnidocysts of five families of sea anemones and found that different samples of the same structure (mentioned as “tissue”) showed differences between the lengths of cnidocysts. Consequently, the mentioned author pointed out that, when sampling cnidocysts by using the classical approach followed to study the cnidom in sea anemones, the section of each structure should be clearly identified.…”
Section: Introductionmentioning
confidence: 99%